The Metabolic Signature of AML Cells Treated With Homoharringtonine - Zhang, Yulong; Li, Na; Chang, Zhiguang; Wang, Huabin; Pei, Hanzhong; Zhang, Dengyang; Zhang, Qi; Huang, Junbin; Guo, Yao; Zhao, Yuming; Pan, Yihang; Chen, Chun; et al. (Frontiers in Oncology, 2022)
Acute myeloid leukemia (AML) is a hematologic malignancy. The overall prognosis is poor and therapeutic strategies still need to be improved. Studies have found that abnormalities in metabolisms promote the survival of AML cells. In recent years, an increasing number of studies have reported the effectiveness of a protein synthesis inhibitor, homoharringtonine (HHT), for the treatment of AML. In this study, we demonstrated that HHT effectively inhibited AML cells, especially MV4-11, a cell line representing human AML carrying the poor prognostic marker FLT3-ITD. We analyzed the transcriptome of MV4-11 cells treated with HHT, and identified the affected metabolic pathways including the choline metabolism process. In addition, we generated a line of MV4-11 cells that were resistant to HHT. The transcriptome analysis showed that the resistant mechanism was closely related to the ether lipid metabolism pathway. The key genes involved in these processes were AL162417.1, PLA2G2D, and LPCAT2 by multiple intergroup comparison and Venn analysis. In conclusion, we found that the treatment of HHT significantly changed metabolic signatures of AML cells, which may contribute to the precise clinical use of HHT and the development of novel strategies to treat HHT-resistant AML.